Does sensation-seeking behavior influence the patterns of flavored e-cigarette use? A cross-sectional study among Indonesian adolescents and young adults - Mouhamad Bigwanto; Melinda Pénzes; Róbert Urbán (BMC, 2024)
Abstract Background The variety of available flavors in e-cigarettes may be a driver for young people to start using these products. The objectives of our study were to examine the relationship between sensation-seeking behavior and e-cigarette use, and to identify the predictors of flavor use patterns among adolescents in Indonesia. Methods Students aged 15 to 24 years participated from randomly selected high schools and universities in Indonesia. Participants answered questions about their demographic data, e-cigarette use, conventional cigarette use, and sensation-seeking. Flavor preferences were identified from eight different flavor categories. Multivariate multinomial regression analysis was employed to predict conventional cigarette and e-cigarette use among students. A latent class analysis was conducted to determine the number of latent classes of flavor use. Results One thousand six hundred high school and university students, with a mean age of 18.2 years (SD 2.19), were recruited between March and August, 2023. Conventional cigarette use in the past 30 days was higher (16.3%) compared to e-cigarette use (13.3%, p = 0.017), with approximately 8.5% of students were being dual users. Higher levels of sensation-seeking significantly increased the odds of being a current e-cigarette user (OR = 2.54, 95%CI 1.99-3.25) and a current conventional cigarette smoker (OR = 2.38, 95%CI 1.85-3.07). Three groups of flavor classes were identified: 1) primarily menthol flavor users (14%), who had a strong association with current conventional cigarette use; 2) experimenters, who mostly preferred fruit-flavored e-cigarettes (76%); and 3) the multi-flavor user group (10%), who had a higher sensation-seeking tendency. Conclusions Flavors, especially menthol and fruit flavors, attract youth, broaden the e-cigarette audience and are particularly appealing to high sensation-seekers. Banning these flavors could significantly deter e-cigarette initiation among youth.